MODERN METHODS OF CAREER GUIDANCE IN TECHNOLOGY (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
This article provides a detailed description of modern methods of career guidance for students in the field of technology. It analyzes the role of innovative pedagogical technologies, interactive methods and practical exercises used in the educational process in developing students' professional interests and abilities. It also considers the issues of combining theory and practice in lessons, and the formation of students' work skills by teaching them independent thinking, creative approach and problem solving. The article also describes effective methods that help students make a conscious choice of their future profession, as well as modern forms and tools of career guidance.